2012
DOI: 10.1016/j.ijgo.2012.09.027
|View full text |Cite
|
Sign up to set email alerts
|

Advancing obstetric anesthesia practices in Georgia through clinical education and quality improvement methodologies

Abstract: A structured program of education and quality improvement led to an increase in the use of regional anesthesia for vaginal and cesarean deliveries. Achievements were sustained during periods of economic and political turmoil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 16 publications
0
23
1
Order By: Relevance
“…The use or RA for CD at the study institutions increased from 20% before their one time, country-wide, multi-institutional intervention to 34% following the program, a rate similar to that reported in year 2015 of the collaboration at CCV. Ninidze et al (10) described better success in their collaboration of yearly program visits over 4 years to five participating hospitals in Georgia, another country with health-care demographics similar to Serbia. The importance of repeated visits over time was emphasized in this study, as the three hospitals who were visited four times reported increases in RA use for CD from approximately 20 to 80%, while the two hospitals visited only twice reported more modest increases from approximately 25 to 50%.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The use or RA for CD at the study institutions increased from 20% before their one time, country-wide, multi-institutional intervention to 34% following the program, a rate similar to that reported in year 2015 of the collaboration at CCV. Ninidze et al (10) described better success in their collaboration of yearly program visits over 4 years to five participating hospitals in Georgia, another country with health-care demographics similar to Serbia. The importance of repeated visits over time was emphasized in this study, as the three hospitals who were visited four times reported increases in RA use for CD from approximately 20 to 80%, while the two hospitals visited only twice reported more modest increases from approximately 25 to 50%.…”
Section: Discussionmentioning
confidence: 99%
“…Obstetricians often have a major influence over patient choice of anesthesia (10). Obstetrician preference may have a larger effect than that of the anesthesiologist in the choice of RA versus GA and efforts directed at obstetrician education to adequately answer patient questions concerning RA may be as important as those directed toward patients in increasing patient acceptance (10). An added benefit is that it may also overcome obstetrician reluctance to RA use (9, 1113, 15).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations